2022
DOI: 10.3390/jsan11030047
|View full text |Cite
|
Sign up to set email alerts
|

Edge Intelligence in Smart Grids: A Survey on Architectures, Offloading Models, Cyber Security Measures, and Challenges

Abstract: The rapid development of new information and communication technologies (ICTs) and the deployment of advanced Internet of Things (IoT)-based devices has led to the study and implementation of edge computing technologies in smart grid (SG) systems. In addition, substantial work has been expended in the literature to incorporate artificial intelligence (AI) techniques into edge computing, resulting in the promising concept of edge intelligence (EI). Consequently, in this article, we provide an overview of the cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 234 publications
0
3
0
Order By: Relevance
“…The choice between the two frameworks depends on factors such as the specific requirements of the project, the level of detail needed, and the area of interest, as well as on their advantages and disadvantages (see Table 1). However, more specific architectures have been designed to address different challenges related to the computational continuum in more depth, such as data management distribution latency and security [2,3,41]. It is worth noting that even though those architectures have benefits related to edge offloading, the implementation can be a complex process and might need significant upfront investment for the initial setup [42,43].…”
Section: Smart-grid Architecturesmentioning
confidence: 99%
See 2 more Smart Citations
“…The choice between the two frameworks depends on factors such as the specific requirements of the project, the level of detail needed, and the area of interest, as well as on their advantages and disadvantages (see Table 1). However, more specific architectures have been designed to address different challenges related to the computational continuum in more depth, such as data management distribution latency and security [2,3,41]. It is worth noting that even though those architectures have benefits related to edge offloading, the implementation can be a complex process and might need significant upfront investment for the initial setup [42,43].…”
Section: Smart-grid Architecturesmentioning
confidence: 99%
“…Molokomme et al proposed an architecture involving multiple components such as residential, commercial, and industrial devices, edge servers, power systems, IoT devices, and the overall cloud infrastructure [3]. The architecture integrates with edge computing, introducing intelligence for analysis, monitoring, and processing of data at the network's edge.…”
Section: Smart-grid Architecturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensors, IoT gadgets, and network connections are the foundation of smart homes Smart grid: This comprises three main systems, namely, generation, transportation, and consumption [18]. The consumer system deploys sensing devices that control and monitor the machines on premises.…”
Section: Challenges With Smart City Applicationsmentioning
confidence: 99%
“…Focussing on improving the conventional Hoepman's eight privacy design strategies, a previous study [218] demonstrated the successful application of such a privacy-preserving mechanism for private and secure IoT services, which included the preservation of data privacy (data collection, storage, and application), user authentication, communication, and computation. Tis simple yet efective design benefts numerous applications, such as identifcation systems, access control systems, smart safety systems, smart grids, and healthcare systems [231].…”
Section: Trustworthy Ai In 5g-based Iot Networkmentioning
confidence: 99%